2021
DOI: 10.3390/educsci11100581
|View full text |Cite
|
Sign up to set email alerts
|

Elementary Students’ Reasoning in Drawn Explanations Based on a Scientific Theory

Abstract: Constructing explanations of scientific phenomena is a high-leverage practice that promotes student understanding. In the context of this study, we acknowledge that children are used to receiving explanations from teachers. However, they are rarely encouraged to construct explanations about the causes and consequences of phenomena. We modified a strategy to elicit and analyze primary students’ reasoning based on scientific theory as a methodological advance in learning and cognition. The participants were four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Even though previous research studies proposed that teachers could move laboratory activities to engender students to be curious before they began learning at the beginning of the chapter (Proulx, 2013;Stefaniak & Turkelson, 2014;Thampi et al, 2020). It is important that the new knowledge must be related to the background that they already know since the explanation of phenomena involves scientific knowledge (Cabello et al, 2021). Similar to other studies, it was indicated that the combination of simulation and physical laboratory was more effective than using them separately (Arıcı & Yılmaz, 2020;Jaakkola et al, 2011;Wang & Tseng, 2018).…”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…Even though previous research studies proposed that teachers could move laboratory activities to engender students to be curious before they began learning at the beginning of the chapter (Proulx, 2013;Stefaniak & Turkelson, 2014;Thampi et al, 2020). It is important that the new knowledge must be related to the background that they already know since the explanation of phenomena involves scientific knowledge (Cabello et al, 2021). Similar to other studies, it was indicated that the combination of simulation and physical laboratory was more effective than using them separately (Arıcı & Yılmaz, 2020;Jaakkola et al, 2011;Wang & Tseng, 2018).…”
Section: Resultsmentioning
confidence: 64%
“…As mentioned earlier, scientific explanations are addressed in most of the features. They have been considered a central practice in classrooms and have become of great interest in science education research (Antonio & Prudente, 2021;Cabello et al, 2021;McNeill & Krajcik, 2008a;McNeill et al, 2004;Nawani et al, 2019;Reiser et al, 2012;Yao & Guo, 2018). Numerous studies in science education research have revealed the strong points of scientific explanations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The precursor models are conceptually reflected both in the morphological characteristics of the actual content of a drawing, as well as in its change, recording development in students' thinking. This is because, in line with oral speech, drawings have the ability, like diagrams, to produce autonomous thinking so that they can share unique meanings (Cabello et al, 2021;Cabello, 2022). Chachlioutaki et al (2016) showed that preschool children, after a relevant didactic intervention on the phenomenon of earthquakes, improved their conceptions by improving, among other things, their drawings for some aspects of the phenomenon.…”
Section: The Role Of Inscriptions In Teaching and Learningmentioning
confidence: 99%
“…Thus, having students creating their own drawings is typically associated with a better understanding than when students learn from visual representations they have been given [3,12]. In particular, collaboratively created drawings provide opportunities for students to integrate multiple representations, exchange and clarify ideas, engage in elaborative discussion, build on each other's ideas, and establish shared representation and deeper science understandings [6,10,11,13,14]. Thus, collaborative drawings have affordances that emerge from both visual representation and the collaborative discourse around drawings' creation.…”
Section: Introductionmentioning
confidence: 99%